Effects of Obtrusive Observation and Rules on Classroom Behavior of Adolescents in a Juvenile Residential Treatment Setting. Issue 5 (September 2021) - Hamrick, Sally A.; Richling, Sarah M.; Brogan, Kristen M.; Rapp, John T.; Davis, William T.
Several studies have used interdependent group contingencies to decrease disruptive behavior and increase appropriate behavior for groups of adolescents. In addition, one study demonstrated that rules plus feedback about rule violations, without additional group contingencies, decreased problem behavior and increased appropriate behavior for adolescents in three classrooms within a residential juvenile facility. Given the rapid behavior change observed in the aforementioned study, it is possible behavior changes were produced by reactivity to obtrusive observation from program implementers. To address this question, we used two A-B designs in conjunction with the conservative dual-criterion (CDC) method to evaluate the extent to which obtrusive observation alone and rules, without systematic consequences, decreased problem behaviors in two classrooms within a residential juvenile facility. Results from visual and CDC analyses indicate that (a) obtrusive observation did not affect problem behavior in either classroom and (b) rules decreased problem behavior in both classrooms and increased appropriate behavior in one classroom. In addition, a measure of social validity indicated that the procedures and outcomes were acceptable to the classroom teacher.